Pengaruh corporate social responsibility (csr) terhadap nilai perusahaan dengan corporate governance sebagai variabel mediasi - Nida, Nida Khoirun Nahda Labibah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research was to determine effect Corporate Social Responsibility or CSR to firm value. Then also to analyze the relationship between CSR and firm value whether it can be mederated by Corporate Governance. This study uses a quantitative approach, to obtain a research sample, it is carried out using a purposive sampling method, the sample is taken by setting certain criteria. The total sample obtained is 17 company samples, the companies must be listed in the Corporate Governance Perception Index (CGPI) ranking and also registered on the Indonesia Stock Exchange (IDX). Then after the data has been collected, analyzed using descriptive analysis and regression analysis using SPSS Statistics 24 software. Based to the research output, indicate that CSR has a significant effect on firm value and as a moderating variable, Corporate Governance is able to strengthen the relationship between CSR and firm value